External Support and Supply-Side Strategies For Sustaining Halal Tourism: An Integrated Analysis - Imas Maesaroh; Hubertina Karolina Ngarbingan; Ike Janita; Ginta Ginting (International Journal of Tourism and Hospitality in Asia Pasific, 2026)
Halal tourism represents a rapidly expanding niche within the global tourism industry, driven by the growing demand for services aligned with Sharia principles. However, ensuring its long-term sustainability remains a critical challenge, particularly from the supply-side perspective. Grounded in integrated theoretical and conceptual frameworks, this study examines how attitudes and perceived risks associated with halal tourism influence product design and business continuity. It further explores how external support such as that provided by government agencies and other stakeholders acts as a moderating variable that strengthens the relationship between supply-side factors (attitudes and perceived risks) and the sustainability of halal tourism enterprises.This study investigates the effects of service providers’ attitudes and perceived risks on product design and business sustainability, while also assessing the moderating role of external support. Employing a quantitative approach with purposive non-probability sampling, data were collected from 310 halal tourism entrepreneurs in the Special Region of Yogyakarta, Indonesia. The relationships among variables were analysed using Structural Equation Modelling (SEM) with Partial Least Squares (PLS). Entrepreneurs’ attitudes toward halal tourism exert a significant influence on product design; however, such attitudes alone are insufficient to ensure long-term business survival. Although perceived risk does not hinder the product design process, it poses a substantial threat to business sustainability. External support has been shown to strengthen the impact of positive attitudes on both product design and business continuity, yet it remains less effective in mitigating the adverse effects of perceived risk. This study contributes theoretically to the growing body of supply-side tourism literature and provides strategic insights for policymakers and halal tourism stakeholders seeking to enhance the competitive advantage and sustainable development of halal tourism destinations.